An Analytical Study Of The Reality Of Educational And Psychological Guidance In Distinguished Schools In Babylon Governorate From The Student’s Point Of View - Marwah Ali Hamzah (Musamus Journal of Physical Education and Sport (MJPES), 2025)
Purpose of this paper is to develop a questionnaire to identify reality of psychological and educational counseling in schools for gifted students in Babylon Governorate, and to identify reality of psychological and educational counseling in these schools from students’ perspective. The researcher adopted descriptive-analytical method, as it is suitable for purposes of this study. research community was defined as students of Gifted Students School in Babylon Governorate for academic year 2024-2025, totaling (751) students. A random sample of (170) students, representing 22.636% of research community, was selected by lottery. The researcher administered questionnaire in its final form, consisting of (25) paragraphs, to 170 students in study sample between December 20, 2024, and December 25, 2024. Questionnaires were then collected, and data from sample’s responses was compiled and statistically analyzed. most important conclusions reached were that psychological counselors in Gifted Students Schools in Babylon possess strong interpersonal skills and ability to build positive relationships with colleagues and students. Furthermore, psychological counselors in Gifted Students Schools in Babylon demonstrate high professional competence and possess interpersonal skills that qualify them to be distinguished counselors. There is also a high demand among students for consultations with psychological counselors at school.